Penerapan model student facilitator and explaining untuk meningkatkan pemahaman konsep energi gerak - Aji, Giri Seno; Winarni, Retno; Wahyuningsih, Siti (Universitas Sebelas Maret, 2020)
The purpose of this research was to improve the understanding ability of the concept of motion energy through the application of the Student Facilitator and Explaining (SFE) model in third-grade students of SD NegeriKarangasem IV No.204 Laweyan District, Surakarta City in academic year 2016/2017. This type of research was classroom action research (CAR) conducted in two cycles. Each cycle was carried out in four stages, consisting of planning, implementation, observation, and reflection. The subjects of this study were third-grade students of SD NegeriKarangasem IV Laweyan Surakarta in the 2016/2017 academic year, totaling 31 students. Data collection techniques in this study consisted of tests, observations, interviews, and documentation. Test validity used technical triangulation and source triangulation. The data analysis technique used an interactive analysis model from Miles &Huberman. The conclusion of this research show that the application of Student Facilitator and Explaining (SFE) models can improve the understanding ability of motion energy concepts in third-grade students of SD NegeriKarangasem IV No.204 Laweyan District, Surakarta City in academic year 2016/2017.